2012
DOI: 10.1093/icvts/ivs027
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of talc poudrage versus pleural abrasion for the treatment of primary spontaneous pneumothorax

Abstract: Primary spontaneous pneumothorax is a pathology mainly affecting healthy young patients. Clinical guidelines do not specify the type of pleurodesis that should be conducted, due to the lack of comparative studies on the different techniques. The aim of this study was to compare talc poudrage and pleural abrasion in the treatment of spontaneous pneumothorax. A retrospective comparative study was performed, including 787 patients with primary spontaneous pneumothorax. The 787 patients were classified into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
2
17
1
1
Order By: Relevance
“…There are no randomised trials assessing the efficacy of talc poudrage at VATS, though a retrospective analysis of 787 patients with PSP treated with bullectomy and either abrasion or talc poudrage demonstrated a shorter hospital stay and surgical time as well as lower complication rates in the group undergoing talc poudrage compared with the group treated with mechanical abrasion. This study also demonstrated a trend towards a lower incidence of recurrence with poudrage than with abrasion (p=0.116) 23. Available data for VATS pleurectomy or mechanical abrasion suggest an incidence of recurrence after these techniques considerably in excess of that reported in our series.…”
Section: Discussionsupporting
confidence: 63%
“…There are no randomised trials assessing the efficacy of talc poudrage at VATS, though a retrospective analysis of 787 patients with PSP treated with bullectomy and either abrasion or talc poudrage demonstrated a shorter hospital stay and surgical time as well as lower complication rates in the group undergoing talc poudrage compared with the group treated with mechanical abrasion. This study also demonstrated a trend towards a lower incidence of recurrence with poudrage than with abrasion (p=0.116) 23. Available data for VATS pleurectomy or mechanical abrasion suggest an incidence of recurrence after these techniques considerably in excess of that reported in our series.…”
Section: Discussionsupporting
confidence: 63%
“…In our case, we used video-assisted thoracoscopic talc insufflation as it has been approved by the FDA and European countries for use in nonmalignant pleural effusions. Talc is extremely safe and has no long-term detrimental effects, making it safe in young, healthy individuals who have no lung impairment, fibrosis, or increased likelihood of cancer or mortality [1820]. Although the use of sclerosing agents is a minimal invasive procedure, it can cause minor complications such as inflammation and infections.…”
Section: Discussionmentioning
confidence: 99%
“…Talc poudrage under thoracoscopy is a safe, cheap and very efficient agent for achieving pleurodesis provided graded talc is chosen for pleurodesis [119,120,141,142]. The recurrence rate seen after talc poudrage is comparable to that seen after mechanical pleurodesis [143][144][145]. Other sclerosing agents given via a chest tube have been used for prevention of pneumothorax, and include bleomycin dextrose, glucose 50%, iodine, tetracycline or talc slurry [146].…”
Section: Indicationsmentioning
confidence: 99%